The contribution of public institutions’ governance in achieving sustainable development: An exploratory study of a sample of public economic institutions in Algeria - Chahrazed, Meghdouri; Lamine, Alloune Mohamed (The International tax journal, 2025)
This study aims to determine the role of governance in public institutions in achieving sustainable development and attempts to apply this to a sample of public economic institutions in Algeria. An exploratory study was conducted using a sample of 144 administrative staff members from the institutions under study, utilizing a questionnaire and the 2020 Excel program for data collection. The Statistical Package for the Social Sciences (SPSS V24) was used for data analysis, interpretation, and results processing. The study employed a descriptive analytical approach and a case study method. The findings revealed that the institutions studied aim to implement public governance principles and mechanisms to seek opportunities to maximize growth and increase resources. However, this can only happen by considering the surrounding economic, social, and environmental factors that help build practices and procedures to meet the sustainable needs of all stakeholders. Corruption was identified as one of the main barriers to institutional growth and sustainability. Therefore, establishing accountability and transparency standards in the field of essential social and environmental services will create a stable investment environment capable of attracting new sources of funds and expanding economic opportunities.